Pengaruh Beberapa Variabel Terhadap Kualitas Laba - Anam, Hairul (Jurnal GeoEkonomi, 2026)
This study aims to examine the effect of capital structure, investment opportunity set and information asymmetry on profit quality. The independent variable consists of capital structure, investment opportunity set and information asymmetry, while the dependent variable is profit quality. The population in this study was 183 manufacturing entities. The sampling technique used was purposive sampling technique. The research sample was 40 samples. The analysis tool uses multiple linear regression analysis method. The results showed that capital structure has an influence on profit quality, the investment opportunity set has no effect on profit quality and information asymmetry has an influence on profit quality.